Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Solve for x:

[tex]\( 3 - 2x = -11 \)[/tex]


Sagot :

Certainly! Let's solve the equation step-by-step for [tex]\( x \)[/tex]:

Given equation:
[tex]\[ 3 - 2x = -11 \][/tex]

Step 1: Isolate the term with the variable [tex]\( x \)[/tex].

We start by subtracting 3 from both sides of the equation to get rid of the constant term on the left side:
[tex]\[ 3 - 2x - 3 = -11 - 3 \][/tex]

This simplifies to:
[tex]\[ -2x = -14 \][/tex]

Step 2: Solve for [tex]\( x \)[/tex].

Now, we need to isolate [tex]\( x \)[/tex] by dividing both sides of the equation by [tex]\(-2\)[/tex]:
[tex]\[ x = \frac{-14}{-2} \][/tex]

When we perform the division, we get:
[tex]\[ x = 7 \][/tex]

Therefore, the solution to the equation [tex]\( 3 - 2x = -11 \)[/tex] is:
[tex]\[ x = 7 \][/tex]